2016
DOI: 10.1111/ajo.12493
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity and associated perinatal outcomes, including stillbirth

Abstract: Women from consanguineous relationships are at higher risk of adverse perinatal outcomes, including stillbirth. Given the 5% prevalence of consanguinity in our obstetric population, these findings have significant implications for preconception counselling, obstetric care and health resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…Congenital abnormalities are a major cause of infant mortality in higher resource environments, with variation between ethnic groups and a strong association with consanguinity [63,64]. Reducing the risks for life-threatening congenital abnormalities [65] (either through the condition itself, or through its association with preterm birth) is dependent on parental awareness regarding the risks of congenital abnormality pre-conceptually, availability and uptake of screening for major congenital abnormalities, the potential for intervention, and parent perspectives on termination of pregnancy, should they carry a baby with a lethal/potentially lethal condition in utero.…”
Section: Reducing the Risks For Congenital Abnormalitiesmentioning
confidence: 99%
“…Congenital abnormalities are a major cause of infant mortality in higher resource environments, with variation between ethnic groups and a strong association with consanguinity [63,64]. Reducing the risks for life-threatening congenital abnormalities [65] (either through the condition itself, or through its association with preterm birth) is dependent on parental awareness regarding the risks of congenital abnormality pre-conceptually, availability and uptake of screening for major congenital abnormalities, the potential for intervention, and parent perspectives on termination of pregnancy, should they carry a baby with a lethal/potentially lethal condition in utero.…”
Section: Reducing the Risks For Congenital Abnormalitiesmentioning
confidence: 99%
“…conducted in Australia, where the consanguinity rate is 5.5%, concluded that parental consanguinity was associated with higher rates of threatened premature labour, fetal congenital abnormality, stillbirth, and perinatal mortality. 5 In that study, consanguinity was also found to be an independent risk factor of nearly 3-fold for stillbirth. In Hong Kong, parental consanguinity is more frequent among non-Chinese ethnic minorities, which account for 8% of the total population.…”
Section: Implications For Clinical Practice or Policymentioning
confidence: 83%
“…Most previous studies have not evaluated the effects of closer consanguinity that might increase risks of hereditary disorders. 5,15,16 To evaluate the effect of degree of inbreeding, comparisons were made among 'first cousin or closer' (including first cousin and double first cousin), 'beyond first cousin' (including first cousin once removed and second cousin), and non-consanguineous relationships.…”
Section: Fig Family Trees Of Consanguineous Marriages With Corresponmentioning
confidence: 99%
“…Another Indian study reported 26.9% of women having history of consanguineous marriage, while the current study reported it to be 19%. Consanguinity is associated with adverse perinatal outcome, pregnancy loss, stillbirths and low birth weight babies [33].…”
Section: Discussionmentioning
confidence: 99%